Description of High-alert Drug Storage Management in Pharmacy Installation of UNS Surakarta Hospital - Pradana, Riska; Karimah, Fine Nur; Sayuti, Nutrisia Aquariushinta (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2024)
Errors in giving first rank drugs in the pharmaceutical field, especially high alert drugs that must be made a top priority. The purpose of this study was to describe the management of high alert drug storage at the Pharmacy Installation at UNS Surakarta Hospital. This research is a descriptive study with a cross sectional approach. Data collection techniques were carried out by direct observation using checklist sheets and interviews with pharmacists based on pharmaceutical service standards in hospitals. The analyzed data is described in the form of words. The results showed that the value of 100% high alert drug list was in the appropriate category, the high alert drug management policy was 85.7% (inappropriate category), stock card recording at the emergency room depot, outpatient and inpatient care was 85.7% and in warehouse 71.4% (inappropriate category). Labeling of high alert drugs in warehouses, emergency department depots, and 80% inpatient and 60% outpatient (categories not suitable). The layout of high alert drug storage is not suitable because inpatient care shows 80% (inappropriate category) and in warehouses, emergency rooms, and outpatient care 100% (appropriate category). Storage temperature and storage system show 100% (appropriate category). Based on the results of the study it can be concluded that the management of high alert drug storage at the Pharmacy Installation at UNS Surakarta Hospital does not meet the standards of pharmaceutical services at the Hospital.